Pengembangan Aplikasi Perangkat Bergerak berbasis Android untuk Diagnosis Penyakit Tanaman Hias Daun dengan Metode Forward Chaining - Dave Putra Radin; Eriq Muhammad Adams Jonemaro; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
During the current pandemic, many people spend their free time doing their own hobbies. One of these hobbies is gardening ornamental plants. Even though you have taken good care of your ornamental plants, ornamental plants can still be exposed to diseases and pests. This causes ornamental plant owners who do not know how to deal with ornamental plant diseases and pests, experiencing losses because their plants can die. From the problems that have been described, this research was carried out to solve these problems by developing a mobile application to diagnose diseases suffered by ornamental leaf plants and provide information on how to overcome these diseases. The application developed in this study has an Android operating system, uses the Firebase Firestore database, and uses waterfall SDLC model. At the requirements analysis stage, an analysis of the requirements needed in the application will be carried out. At the planning phase, it will explain the results of interface design that will be used to carry out the implementation phase. At the implementation stage, it will explain the results of the implementation carried out on the application. After the implementation phase has been completed, the testing phase will be carried out. At the testing phase, 3 kinds of tests will be carried out. The first test is validation test, using the blackbox testing method and getting valid results. The second test, namely usability testing, was carried out using the SUS method and got a total score of 460 and an average score of 92 which means that score is include in acceptable category and grade A. The third test, namely compatibility testing, is carried out by testing the application on 5 devices that have different versions of the Android operating system and getting valid results. From the results of the three tests, it shows that the functional and non-functional requirements of the system have been successfully created with satisfactory results.